Abelian reductions of deformed N=4 SYM - Cardona, Carlos [UNESP]; Lopez-Arcos, Cristhiam; Nastase, Horatiu [UNESP] (Elsevier, 2015)
Following the work in [1], where the massive ABJM model in 2+1 dimensions was shown to have an abelian reduction to the relativistic Landau-Ginzburg, and motivated by the implications for condensed matter through AdS/CFT, we show that a FI deformation of N=4 SYM in 3+1 dimensions with a mass term can also be reduced to a relativistic Landau-Ginzburg model, with the possibility of coupling it to a real scalar, whereas the simply mass deformed N=4 SYM reduces only to a massive ϕ4 model (scalar QED) coupled to a real scalar. We study the classical solutions of the model, in particular vortex solutions.